Disability poverty and ageing in regional Australia: The impact of disability income reforms for indigenous Australians - Soldatic, Karen (Australian Social Policy Association, 2018)
© 2018 Australian Social Policy Association Australian disability policy has undergone considerable reform since the early 2000s. While recent research and scholarship has largely focused on the new National Disability Insurance Scheme, there is a dearth of research that examines the impact of reform to the Disability Support Pension, and even less so the effects on Indigenous Australians living with disability. This is surprising as a higher proportion of Indigenous Australians live with disability than the non-Indigenous population. This article pays particular attention to the experiences of Aboriginal Australians who have acquired a disability after extensive years of working (25–40 years), yet are still of workforce age (less than 65 years of age). Because of tightened eligibility criteria for the Disability Support Pension, people in this group are placed onto the lower paid Newstart Allowance (general unemployment benefit). The article illustrates the high levels of poverty that Aboriginal Australians with disabilities experience daily, and the ongoing costs they incur in managing Newstart conditionality to maintain continued access to the general unemployment benefit.